2020
DOI: 10.1016/j.pmedr.2020.101178
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of teacher-delivered nutrition education programs on elementary-aged students: An updated systematic review and meta-analysis

Abstract: Research shows that schools can make a positive impact on children’s nutritional outcomes. However, it is also reported that schools and teaching staff note many barriers, which may restrict nutritional education programming and delivery. This is concerning, considering the view that teachers are the key agents for promoting health and nutrition within schools. The purpose of the updated systematic review and meta-analysis was to ascertain the impact that nutrition education programs have on elementary-aged st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 61 publications
(154 reference statements)
1
27
1
5
Order By: Relevance
“…The program was reported by children and parents to have good acceptance and benefits, attendance at activities was high and retention was close to 100%. In previous studies, the interventionists in charge of implementing the program have usually been school teachers, which suggests a greater potential for its application in schools [ 39 ]. In our study, however, the intervention was implemented by interns of Nutrition and Physical Activity undergraduate programs who have a greater knowledge of their respective subject areas, which could be related to better results.…”
Section: Discussionmentioning
confidence: 99%
“…The program was reported by children and parents to have good acceptance and benefits, attendance at activities was high and retention was close to 100%. In previous studies, the interventionists in charge of implementing the program have usually been school teachers, which suggests a greater potential for its application in schools [ 39 ]. In our study, however, the intervention was implemented by interns of Nutrition and Physical Activity undergraduate programs who have a greater knowledge of their respective subject areas, which could be related to better results.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-country data indicated that local school contexts have a significant impact on children's daily MVPA accumulation pattern [34]. Recent systematic reviews and meta-analysis suggest that nutrition interventions can have a positive influence on children's nutritional knowledge and children's energy intake [35,36]. However, The National Institute of Clinical Excellence (NICE) has highlighted disparities in the evidence, specifically the need for evaluation of multi-component interventions that aim to reduce obesity-related behaviours in children [37].…”
Section: Introductionmentioning
confidence: 99%
“…Teachers are expected to work together with parents so that the development of children at home can continue in school supported by routine activities for independent study. (Lydia, M., Nina, NK, Wayan, D., Rambat Nur, S., & Lutfi Firdaus, M, 2018) A literature study conducted by Cotton, W., Dudley, D., Peralta, L., & Werkhoven, T (2020) shows that teaching nutrition education in primary schools by qualified teachers can make an important contribution to children's knowledge and eating habits. Small and medium effect sizes suggest that careful, evidence-based decisions need to be made by policymakers and pedagogies regarding the teaching strategies used when delivering nutrition education programs to primary-age students.…”
Section: The Role Of Family and Teachersmentioning
confidence: 99%